-(.625)(5x)(1.6)(12y)(0)=

Simple and best practice solution for -(.625)(5x)(1.6)(12y)(0)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(.625)(5x)(1.6)(12y)(0)= equation:


Simplifying
-1(0.625)(5x)(1.6)(12y)(0) = 0

Remove parenthesis around (5x)
-1 * 0.625 * 5x(1.6)(12y)(0) = 0

Remove parenthesis around (12y)
-1 * 0.625 * 5x * 1.6 * 12y(0) = 0

Reorder the terms for easier multiplication:
-1 * 0.625 * 5 * 1.6 * 12 * 0x * y = 0

Multiply -1 * 0.625
-0.625 * 5 * 1.6 * 12 * 0x * y = 0

Multiply -0.625 * 5
-3.125 * 1.6 * 12 * 0x * y = 0

Multiply -3.125 * 1.6
-5 * 12 * 0x * y = 0

Multiply -5 * 12
-60 * 0x * y = 0

Multiply -60 * 0
0x * y = 0

Anything times zero is zero.
0x * y = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5(1x+6)+13=5x+43 | | 9-5+1=15 | | 5x-4forx=3 | | 3xx=6 | | 47=3x+5 | | (3x-7)(x-4)=0 | | -6x+12=-5x+19 | | 3x-4iy=9+22i | | 7+2x-x=9+3x | | -22+26= | | 65=-5x-10 | | 2-24+12+4= | | (.25)(5.3x)(-4)(y)(1)= | | -(4x-8)=-6x+18 | | 27p=837 | | -3(1x+12)=-8x-31 | | 806=17t-78 | | (2x-1)=75 | | -(.75)(-8)(.75)(4)(1)= | | -8(1-k)=-16 | | t-11=21 | | 9-5-3+9= | | 6(1x-2)+18=-2x+46 | | X+5-1=5 | | -(.75)(-8x)(.75)(4y)(1)= | | 900=1+31n | | -5=3v+3-v | | -8(1x+4)=-112 | | 5+3t=38 | | 3*x^3-6*x^2+x-7=0 | | x^2-110-x=0 | | 2(x+1)=-2x+2 |

Equations solver categories